Metastatic gallbladder adenocarcinoma in a cat - Pandolfo, Gustavo Willian; Teixeira, Marcela Bruggemann de Souza; Cristo, Thierry Grima de; Gaspar, Taís; Carniel, Felipe; Casagrande, Renata Assis (Brazilian Journal of Veterinary Pathology, 2023)
Biliary neoplasms are uncommon in cats and affect older animals. A 12-year-old female crossbreed cat showed prostration, lethargy, apathy, and severe jaundice. Ultrasonography showed distention of the gallbladder associated with severe obstruction of the bile ducts with thickening of the biliary wall, forming amorphous masses of irregular contour and heterogeneous appearance directed to the lumen measuring up to 2 cm. Necropsy showed a gallbladder with a yellowish and soft nodule measuring 3 × 3 cm, compressing the extrahepatic bile duct, occluding the passage of bile. There were also firm, yellowish multifocal to coalescing nodules in the liver, ranging from 0.5 to 1 cm, affecting 10% of the organ, in addition to lungs with firm, yellowish multifocal nodules ranging from 0.2 to 0.5 cm, affecting 20% of the organ. Histologically, gallbladder and bile ducts had malignant epithelial neoplastic proliferation, which was organized into multiple papillary and ductal projections, separated by moderate fibrovascular stroma compatible with gallbladder adenocarcinoma. The liver and lungs also contained neoplastic structures with a ductal appearance and papilliform projections identical to those observed in the gallbladder. The immunohistochemical examination (IHC) showed intense positive staining of epithelial neoplastic cells for pan-cytokeratin (AE1/AE3) and no staining for vimentin (Clone V9). The diagnosis of gallbladder adenocarcinoma with metastasis in the liver and lungs was established based on the clinical, macroscopic, histopathological, and immunohistochemical findings.